Penglibatan Masyarakat Dalam Pemuliharaan Kawasan Warisan Di Pusat Bandaraya Ipoh, Perak - Mamat, Mohd Jaki (2014)
This research focuses on the problems of abandoned heritage sites by the community, administrators, users and building owners. To overcome these problems, two main aspects are measured to evaluate the community’s acceptance level in stirring the efforts to conserve the sites. Potential and awareness are the two aspects that become as main objective in this research. The potential aspect was measured by evaluating the community’s confidence and understanding level towards the heritage sites and how it could encourage the community to conserve these sites. Penyelidikan ini memberi fokus kepada masalah pengabaian kawasan warisan di kalangan masyarakat, merangkumi pentadbir, pengguna dan pemilik bangunan. Bagi mengatasi masalah ini dua aspek utama diukur untuk menilai tahap penerimaan masyarakat dalam menggerakkan usaha pemuliharaan di kalangan mereka. Dua aspek dimaksudkan ialah potensi dan kesedaran yang menjadi objektif utama penyelidikan ini.